1979
DOI: 10.1017/s0021859600086329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Texel-and Suffolk-sired lambs out of Finnish Landrace × Dorset Horn ewes under grazing conditions

Abstract: Two hundred and ten Finn-Dorset ewes were mated to ten rams, five Suffolks and five Texels, in 2 years, to evaluate Texel rams as fat lamb sires. Three hundred and ninetyseven lambs were born and used in the study until the 6th week of age, after which 155 lambs were available for the rest of the experiment. From 6 weeks of age they were grazed with their dams and weighed weekly until slaughtered at 30 kg (females) or 36 kg (males) live weight. Carcasses were assessed by the Meat and Livestock Commission and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0
3

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
4
3
0
3
Order By: Relevance
“…In our study lambing occurred on pasture, whereas in Leymaster and Jenkins (1993) experiments lambing occurred in drylots. However, our results are similar to More O'Ferrall (1974) Initial weight ( and Latif and Owen (1979). More O'Ferrall (1974) reported nonsignificant differences for the perinatal survival of 91.6 and 90.1% for Suffolk and Texel sired lambs, respectively, and Latif and Owen (1979) reported the survival of 89.6% for Suffolk and 90.4% for Texel crossbred progeny.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In our study lambing occurred on pasture, whereas in Leymaster and Jenkins (1993) experiments lambing occurred in drylots. However, our results are similar to More O'Ferrall (1974) Initial weight ( and Latif and Owen (1979). More O'Ferrall (1974) reported nonsignificant differences for the perinatal survival of 91.6 and 90.1% for Suffolk and Texel sired lambs, respectively, and Latif and Owen (1979) reported the survival of 89.6% for Suffolk and 90.4% for Texel crossbred progeny.…”
Section: Resultssupporting
confidence: 89%
“…However, our results are similar to More O'Ferrall (1974) Initial weight ( and Latif and Owen (1979). More O'Ferrall (1974) reported nonsignificant differences for the perinatal survival of 91.6 and 90.1% for Suffolk and Texel sired lambs, respectively, and Latif and Owen (1979) reported the survival of 89.6% for Suffolk and 90.4% for Texel crossbred progeny. Vesley et al (1966) reported equal survival rates for purebred Suffolk and Columbia progeny (85.3 and 89.5%, respectively).…”
Section: Resultssupporting
confidence: 89%
“…Females were slaughtered at 30 kg live weight and males at 36 kg. Although growth rate differences between Texel-and Suffolk-cross lambs were small in the present study, the trends observed agree with those reported elsewhere (ABRO, 1975;More O'Ferrall and Timon, 1977a;Latif and Owen, 1979), under grazing conditions. Carcasses were classified for fatness and conformation (Meat and Livestock Commission, 1975).…”
supporting
confidence: 92%
“…Carcasses of such lambs, however, are frequently reported to be over-fat or to have unacceptably soft subcutaneous fat (Robinson and 0rskov, 1975;0rskov, 1976). Recent work has shown that carcasses of Texel-sired lambs contain less fat and more lean than carcasses of lambs sired by many other breeds (Animal Breeding Research Organisation, 1975;More O'Ferrall and Timon, 1977b;Latif and Owen, 1979). Recent work has shown that carcasses of Texel-sired lambs contain less fat and more lean than carcasses of lambs sired by many other breeds (Animal Breeding Research Organisation, 1975;More O'Ferrall and Timon, 1977b;Latif and Owen, 1979).…”
mentioning
confidence: 99%
“…Esses valores podem ser considerados bons, sendo equivalentes àqueles registrados por MACEDO (1998). Os rendimentos verdadeiro e comercial são equivalentes àqueles apresentados por outros autores, em estudos com cordeiros (LATIF e OWEN (1980), SAÑUDO et al (1981), SAÑUDO e SIERRA (1986), GUNEY (1989), MARTINS (1997) Tabela 3 -Médias para peso na origem (PO), no abate (PA), perda de peso da origem ao abate (PPO), peso da carcaça quente (PCQ), peso da carcaça fria (PCF), perda de peso por resfriamento (PPR), rendimento de origem (RO), rendimento verdadeiro (RVC), rendimento comercial (RCC), índice de compacidade da carcaça (ICC) e índice de compacidade do pernil (ICP), conforme o tratamento 1313 REIS et al e MACEDO (1998). Não se observaram diferenças nos índices de compacidade da carcaça entre os tratamentos, sendo que os valores obtidos se encontram próximos aos citados por SAÑUDO et al (1981), que é de 201,84.…”
Section: Resultsunclassified